STUDY OF SANDWICH PANEL APPLICATION ON SIDE HULL OF CRUDE OIL TANKER - Ismail, Abdi; Zubaydi, Achmad; Piscesa, Bambang; Tuswan, Tuswan; Ariesta, Rizky Chandra (Journal of Applied Engineering Science, 2021)
A lightweight sandwich plate system (SPS) consisted of steel faceplate and polyurethane elastomer composite cores have excellent potential to be applied on the ship structure. Steel faceplate and polyurethane elastomer (PU) cores are frequently applied, but PU has a relatively high material cost. More economical material can be achieved by combining PU with fiberglass as a fiberglass reinforced polyurethane elastomer (FRPU) composite. In this study, the sandwich consisting of steel faceplate and FRPU composite core material is applied in the tanker side hull by investigating the structural performance and weight saving analysis using finite element analysis (FEA). Four sandwich side hull models using different stiffener configurations are compared with the conventional stiffened plate model. The result shows the promising SPS application in terms of structural strength and weight savings. The remarkable stress reduction, deformation, and structural weight reduction due to SPS application are discussed. Therefore, its weight reduction can increase the ship payload so that ship operations will be cost-effective.